2004
DOI: 10.1159/000077332
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Serum Nitric Oxide, Malondialdehyde Levels, and Antioxidant Enzyme Activities in Behçet’s Disease with and without Ocular Disease

Abstract: Objective: The pathogenesis of Behçet’s disease (BD) may be related to excessive production of reactive oxygen species, activated neutrophils, and T lymphocytes. The goal of this prospective study was to investigate whether there is any relationship among the oxidant/antioxidant system and nitric oxide (NO) and malondialdehyde (MDA) levels in patients with BD and its subtypes: complete Behçet’s disease (CBD) and incomplete Behçet’s disease (ICBD), with or without ocular disease. Methods: Thirty-two patients an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 25 publications
0
8
0
1
Order By: Relevance
“…reported that serum NO levels are not significantly changed in patients with BD and its subtypes,[29] whereas others reported decreased NO levels in the serum of BD patients. [3016] Orem et al .…”
Section: Discussionmentioning
confidence: 99%
“…reported that serum NO levels are not significantly changed in patients with BD and its subtypes,[29] whereas others reported decreased NO levels in the serum of BD patients. [3016] Orem et al .…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress is also associated with other autoimmune diseases, such as scleroderma, type 1 diabetes mellitus, and Behçet's disease (21)(22)(23). However, the exact relationship between these two situations is still undefined.…”
mentioning
confidence: 99%
“…In another study, which investigated the oxidant-antioxidant status in whole blood from BD and controls, GPx was found to be decreased similarly to the previous paper. 8 Aydin et al 24 found increased malondialdehyde levels, decreased GPx activity and non-significant changes in SOD activity in the serum of the patients. SOD activity was demonstrated to be increased in erythrocyte from BD patients in another study.…”
Section: Discussionmentioning
confidence: 95%